Brewing Tensions: The Colonial Gaze of the German–Namibian Publishing Industry - Tycho Alexander van der Hoog (Africa Spectrum, 2022)
The call to decolonize African Studies has a profound influence on the field, with varying degrees of success. This article addresses this topic in relation to the author’s personal experiences in the publishing industry in Namibia. By describing the attempt to publish a historical book about Namibian beer with a well-known German–Namibian publishing house, the lingering power of German–Namibian settler colonialism becomes clear. This article renders visible the power structures within the Namibian book market that perpetuates a whitewashed version of Namibian history and argues that decolonizing knowledge cannot succeed without paying attention to the (private) publishing industry.